LEXICAL COHESION USED IN FOLKLORE “LITTLE RED RIDING HOOD“ - Lutfiah Widyaningrum; Silpia Rahayu (PROJECT (Professional Journal of English Education), 2022)
Communication is one of the most interactions that are often carried out as Social beings. This communication can be done if both speaker and listener can convey and understand their thoughts by using language. Language can be learned through discourse that includes all spoken or written text. The study of language in use is known as discourse analysis. The most important part of discourse analysis especially for written discourse is Cohesion which is divided into grammatical and lexical cohesion. There are two main types in lexical cohesion: reiteration and collocation. The researchers chose folklore as an object of research since it is a type of written discourse. The objective of this research is to identify the types of lexical cohesion that occur often in folklore. The subject of this research is “Little Red Riding Hood” folklore written by Leanne Guenther. This research uses descriptive qualitative methods and focuses on lexical cohesion, namely repetition and synonymy. The instrument that the researchers used are other journals, articles, electronic sources, and several other helpful resources. According to the findings of this research, “Little Red Riding Hood” folklore contains thirteen types of lexical cohesion, which include six repetitions and seven synonyms. Therefore, the average between repetition and synonym is almost equal. Keywords:  Discourse Analysis, Lexical Cohesion, Repetition, Synonym